2022
DOI: 10.1111/scd.12762
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic radiographs and dental patients with Down syndrome: A scoping review

Abstract: Introduction: Life expectancy for people with Down syndrome (DS) has increased to 60 years, although poor oral health affects their quality of life. Panoramic radiographs (PRs) are usually well-tolerated by people with DS and can provide valuable diagnostic data for treatment planning and research. Methods A scoping review of peer-reviewed articles published between 1971and 2021 was conducted in accordance with the PRISMA extension for scoping reviews to determine the scope of use of PRs for people with DS.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 103 publications
(224 reference statements)
0
2
0
Order By: Relevance
“…However, surprisingly, no patients with genetic or syndromic conditions were diagnosed with edentulism in this study, whereas other studies have reported various cases of hypodontia and hyperdontia in this group. [ 24 25 ] Hence, the findings of this study suggest further investigation of the SCD clinic’s data, which is required to identify appropriate diagnosis and management of the patients seen.…”
Section: Discussionmentioning
confidence: 96%
“…However, surprisingly, no patients with genetic or syndromic conditions were diagnosed with edentulism in this study, whereas other studies have reported various cases of hypodontia and hyperdontia in this group. [ 24 25 ] Hence, the findings of this study suggest further investigation of the SCD clinic’s data, which is required to identify appropriate diagnosis and management of the patients seen.…”
Section: Discussionmentioning
confidence: 96%
“…This susceptibility is attributed to factors such as cognitive disability, reduced manual dexterity, and a tendency to be uncooperative with treatment [38•, 39••]. Moreover, DS individuals often exhibit higher plaque indices compared to non-syndromic individuals, which can be exacerbated by dental abnormalities like peg-shaped teeth and dental crowding/malocclusion [40,41]. Nevertheless, oral hygiene may be deemed satisfactory in individuals, typically children aged 10 years or younger, who receive assistance with toothbrushing from their parents or caregivers [42].…”
Section: Susceptibility To Periodontal Diseasesmentioning
confidence: 99%